2017
DOI: 10.3892/etm.2017.4808
|View full text |Cite
|
Sign up to set email alerts
|

Effects of insulin-like growth factor 1 and basic fibroblast growth factor on the morphology and proliferation of chondrocytes embedded in Matrigel in a microfluidic platform

Abstract: Abstract. An integrated microfluidic device was utilized in the present study to investigate the morphology and proliferation of rabbit articular chondrocytes embedded in Matrigel in the presence of insulin-like growth factor 1 (IGF-1) and/or basic fibroblast growth factor (bFGF). The microfluidic device was composed of two parallel channels and a central perfusion-based three-dimensional cell culture module. The rabbit chondrocytes were cultured for 2 weeks at series of concentration gradients of IGF-1 and/or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 41 publications
1
5
0
Order By: Relevance
“…In addition, IGF-1 also plays important roles in cartilage repair that can promote chondrocyte survival, proliferation, and production of cartilage matrix [25]. Due to these characteristics, IGF-1 has garnered considerable interest for OA therapy and showed great potential for clinical translation [26][27][28]. Herein, we transfected ADSCs with IGF-1 modRNA, characterized the expression pattern of IGF-1-ADSC and explored its potential therapeutic effect in a murine OA model.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, IGF-1 also plays important roles in cartilage repair that can promote chondrocyte survival, proliferation, and production of cartilage matrix [25]. Due to these characteristics, IGF-1 has garnered considerable interest for OA therapy and showed great potential for clinical translation [26][27][28]. Herein, we transfected ADSCs with IGF-1 modRNA, characterized the expression pattern of IGF-1-ADSC and explored its potential therapeutic effect in a murine OA model.…”
Section: Introductionmentioning
confidence: 99%
“…Microfluidic devices have been used to culture hydrogels in dynamic conditions, thus creating shear forces and concentration gradients which help to recapitulate the endogenous environment. Li et al 101 reported the use of such a device to screen the combinatorial effects of two growth factors on type II collagen production in Matrigel-encapsulated chondrocytes. Immunostaining of the entire polydimethylsiloxane (PDMS) chip, with the aid of image analysis software, allowed for rapid data acquisition.…”
Section: Hydrogelsmentioning
confidence: 99%
“…As the most recent advancement in the palette of 3D culture techniques, organ-on-a-chip (OOAC) and microphysiological systems (MPS) aim for an even better recapitulation of a native tissue-like environment, tissue architecture and cell-specific responses relevant to OA modeling by combining stem cell or patient-derived primary cell-based models for cartilage and synovium ( Fomby et al, 2010 ; Smeriglio et al, 2015 ; Tian et al, 2016 ; Li et al, 2017 ; Lin et al, 2019 ) as well as adipose ( Loskill et al, 2017 ) and bone-like tissues ( Mansoorifar et al, 2021 ; Nasello et al, 2021 ). In this context, microfluidic technologies can create an even more dynamic yet more controllable musculoskeletal disease microenvironment.…”
Section: In Vitro Technologies To Model the Cellular And Mic...mentioning
confidence: 99%